Systematic Identification and Functional Analysis of Circular RNAs During Rice Black-Streaked Dwarf Virus Infection in the Laodelphax striatellus (Fallén) Midgut - Zhang, Jianhua; Wang, Haitao; Wu, Wei; Dong, Yan; Wang, Man; Yi, Dianshan; Zhou, Yijun; Xu, Qiufang (Frontiers in Microbiology, 2020)
Circular RNAs (circRNAs) are endogenous RNAs that have critical regulatory roles in numerous biological processes. However, it remains largely unknown whether circRNAs are induced in response to plant virus infection in the insect vector of the virus as well as whether the circRNAs regulate virus infection. Rice black-streaked dwarf virus (RBSDV) is transmitted by Laodelphax striatellus (Fallén) in a persistent propagative manner and causes severe losses in East Asian countries. To explore the expression and function of circRNAs in the regulation of virus infection, we determined the circRNA expression profile in RBSDV-free or -infected L. striatellus midgut tissues by RNA-Seq. A total of 2,523 circRNAs were identified, of which thirteen circRNAs were differentially expressed after RBSDV infection. The functions of these differentially circRNAs were predicted by GO and KEGG pathway analyses. The expression changes of five differentially expressed circRNAs and eight parental genes were validated by RT-qPCR. The circRNAs-microRNAs (miRNAs) interaction networks were analyzed and two miRNAs, which were predicted to bind circRNAs, were differentially expressed after virus infection. CircRNA2030 was up-regulated after RBSDV infection in L. striatellus midgut. Knockdown of circRNA2030 by RNA interference inhibited the expression of its predicted parental gene phospholipid-transporting ATPase (PTA) and enhanced RBSDV infection in L. striatellus. However, none of the six miRNAs predicting to bind circRNA2030 was up-regulated after circRNA2030 knockdown. The results suggested that circRNA2030 might affect RBSDV infection via regulating PTA. Our results reveal the expression profile of circRNAs in L. striatellus midgut and provide new insight into the roles of circRNAs in virus-insect vector interaction.